Review on Micro Power Energy Harvesting by Using Smart Materials - Hari, Kamble Shirkant; Shivaji, Chougale Dayanand; Jabade, S. I. (Asian Review of Mechanical Engineering, 2015)
Energy is one of the most important things in this century. Energy is essential for the powering business, industrialized and the shipping of good and service to serve world economies. The running most of our appliance and to carry out daily work we need electricity. It’s really very difficult to imagine our life without electricity, our life would really stop so there is high need, to produce electricity and find some other feasible method to produce electrical energy. Now day’s people have been an increases demand on low power and portable device like smart phone, IPods, etc. Therefore then need low power and portable energy source. In this scope piezoelectric and thermocouple materials become strong devices for energy generation and use in future applications. In this review paper discuss the use of piezoelectric and thermocouple for natural energy harvesting for a low power consumption.